Toxin-antitoxin genes are differentially expressed in Escherichia coli relA and spoT mutans cultured under nitrogen, fatty acid, or carbon starvation conditions - Maciąg-Dorszyńska, Monika; Olszewski, Paweł; Karczewska, Monika; Boss, Lidia (Frontiers in Microbiology, 2025)
IntroductionThe stringent response is one of the fundamental mechanisms that control and modulate bacterial adaptation to stress conditions, such as nutrient limitation. The accumulation of stringent response effectors, (p)ppGpp, causes differential expression of approximately 500 genes, including genes of bacterial endogenous toxin-antitoxin (TA) systems. However, the exact link between (p)ppGpp and toxin-antitoxin systems’ activation, as well as toxin-antitoxin role in stress adaptation remains disputed.MethodsIn this study, we performed a complex analysis of changes (RNA-Seq) in the toxin-antitoxin operons’ transcription in response to nitrogen, fatty acid, or carbon starvation, in bacteria with different abilities of (p)ppGpp accumulation.Results and discussionAlthough we observed that in some cases (p)ppGpp accumulation appears to be crucial for transcriptional activation of TA genes (e.g., ghoST, ryeA), our data indicates that the general pattern of chromosomally encoded TA gene expression in E. coli differs depending on the nutrient distribution in the environment, regardless of the alarmone accumulation.